PERAN MAHKAMAH KONSTITUSI SEBAGAI PENGAWAL DEMOKRASI DI INDONESIA - Rommy Patra (Jurnal Komunikasi Hukum, 2022)
The role of the Constitutional Court (MK) as the guardian of democracy can be seen from its decisions related to judicial review and dispute resolution on election results. Problems: (1) What is the role of the Constitutional Court in guarding democracy in Indonesia so far? (2). How to increase the role of the Constitutional Court as the guardian of democracy in Indonesia? This writing uses a normative juridical method. The results of the study, the role of the Constitutional Court as the guardian of democracy: (1) the indicators are judicial review decisions that contribute to the development of democracy in Indonesia, such as Decision: No. 011-017/PUU-I/2003; No. 013-022/PUU-IV/2006; No. 013-022/PUU-IV/2006; No. 6/PUU-V/2007 and others. Meanwhile, the Constitutional Court's Decision regarding the resolution of disputes over the phenomenal election results is Decision No. 41/PHPU.D-VI/2008 which applies the concept of systematic, structured and massive election violations. However, there is also a conservative Constitutional Court Decision in Decision No. 51-52-59/PUUVI/2008 and Decision No. 53/PUU-XV/2017 where the Constitutional Court rejected the request to cancel the presidential threshold. (2) to increase its role, the Constitutional Court must develop a consistent pattern of decision-making to realize constitutional justice and not only rely on formal legality.